Validasi Flashcard BlaaBlaaBlaa sebagai media intervensi gangguan speech delay - Wibowo, Clarissa Serena; Mulia, Intan Prameswari Putri; Lo, Valencia; Royani, Widya Annisa; Yulianto, Jony Eko (INDRA: Jurnal Pengabdian kepada Masyarakat, 2024)
The global pandemic has been disrupting the lives of many people. For children aged 2-4 years old with speech delay disorder, social isolation can be detrimental because there is a lack of social interactions that are vital for their language development. This article focused to develop an intervention media, the Blaablaablaa Flashcard, to help parents and therapists working with children with speech delay. In developing this paper, we document the process of validating the cards by working with developmental psychologists and two therapists in Surabaya. In the process, we also explore the potential improvements that can be made to improve the quality of the cards. Various feedback has been gathered, ranging from the content, design, and instructional elements. Results show that the Blaablaablaa Flashcard meets the standard to use as an intervention media for children with speech delay.